2008
DOI: 10.1007/s12217-008-9037-0
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopic Analysis of Cupriavidus metallidurans LMG 1195 (CH34) Cultured in Low-shear Microgravity Conditions

Abstract: In this study, the effect of low-shear microgravity on the metabolism of Cupriavidus metallidurans LMG 1195 was studied with Raman spectroscopy. Therefore, the strain was cultured for 24 or 48 h in a rotating wall vessel to simulate microgravity (SMG) and in a control setup. The differences in Raman spectra recorded from both setups after 24 h of culturing were small. The most prominent features in a difference spectrum, calculated between the mean spectra from the microgravity and the control setup separately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Interestingly, PHB synthesis in CH34 is initially (i.e., after 24 hours of growth) enhanced under simulated microgravity [41]. The CH34 genome has three copies of phaC , one copy each of phaA and phaP , three copies of phaB , and one regulatory gene phaR (for Rmet numbers see Table S9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, PHB synthesis in CH34 is initially (i.e., after 24 hours of growth) enhanced under simulated microgravity [41]. The CH34 genome has three copies of phaC , one copy each of phaA and phaP , three copies of phaB , and one regulatory gene phaR (for Rmet numbers see Table S9).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have noted changes in gene expression, cell morphology and physiology for C. metallidurans CH34 cells in response to spaceflight (i.e. cells grown at the International Space Station during 10-day visits) and oxidative stress [41] , [42] , as well as simulated microgravity and ionizing radiation (unpublished). The organism has been isolated from very harsh environments such as ultra-clean spacecraft assembly rooms [43] and spent-nuclear-fuel pools [44] .…”
Section: Introductionmentioning
confidence: 99%
“…In the study of De Gelder et al [ 21 ], the yield of poly-β-hydroxybutyrate (PHB) produced by Cupriavidus metallidurans LMG 1195 under LSSMG conditions in the RWVs was reported to be increased after 24 h of culture, while after 48 h of culture, the PHB concentrations were reduced in SMG compared to in the control. In the study of Benoit et al [ 5 ], the production of actinomycin D by Streptomyces plicatus WC56452 in space was reported to be increased by 15.6 and 28.5% on days 8 and 12, respectively, but decreased in all subsequent matched sample points (16–72 d at intervals of 4 d) compared to the ground controls.…”
Section: Effect Of Spaceflight and Simulated Microgravity On Microbiamentioning
confidence: 99%
“…However, the different mechanisms by which they respond and adapt to these environments (especially to microgravity in space) remain unclear. Recently, spaceflight and ground simulated microgravity (SMG) or low-shear modeled microgravity (LSMMG) experiments have demonstrated that microgravity can affect cellular processes and functions in microorganisms, such as cell growth [ 6 9 ], gene expression [ 10 12 ], cell morphology and development [ 13 , 14 ], virulence and resistance [ 15 18 ], biofilm formation [ 19 , 20 ], secondary metabolism [ 21 23 ], and microbial mutations and relation to adaptation to LSMMG [ 24 ]. Considerable effort has been focused on cell growth and secondary metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…de Gelder et al . (2009) demonstrated increased production of poly-β-hydroxybutyrate by C. metallidurans LMG 1195 after 24 h of cultivation under LSSMG conditions but reduction after 48 h of culture compared to 1 × g controls, indicating fluctuation of metabolite production in microgravity. No simulated-microgravity-related changes in the production of secondary metabolites (e.g.…”
Section: Experiments In Space and Ground-based Space Simulation Facilmentioning
confidence: 99%